ASSESSMENT DEVELOPMENT TO MEASURE SCIENCE PROCESS SKILLS ON THE INTERACTION OF LIVING THINGS WITH THEIR ENVIRONMENT IN JUNIOR HIGH SCHOOL - Della Oktavia; Ahmad Walid (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
This study aims to develop an assessment to measure science process skills on living things interaction and their environment. The research used research and development (R&D) that consist research and initial information collection, planning, initial product format development, small-scale trials, product revisions, initial trials, and final products. The trial subjects were expert subjects (assessment experts, material experts and linguists), and the subjects were students of state junior high school in Bengkulu City as product users. Data were analyzed descriptive qualitatively and quantitatively. Feasibility assessment by three validator experts developed on the assessment aspect of 89%, material aspect of 93%, and language aspect of 93%, overall was declared very feasible with an average of 92%. This showed that the assessment of science process skills to measure science process skills was stated to be very suitable to be used to measure the level of students' science process skills. This assessment was the science assessment, where in the development of the science assessment used formative assessment because this assessment was given to every lesson and can be carried out on sub-subjects or each subject. In the development of this formative assessment, multiple choice tests were developed.